Design guideline for extended pile shaft incorporating nonlinear pile-soil interaction. (1st January 2022) - Heidari, Mehdi; Hesham El Naggar, M.
Abstract: Equivalent fixed-based cantilever approach is commonly used for seismic performance-based design of pile foundations supporting marine and bridge structures. In this method, prior knowledge of parameters such as equivalent length of fixity, depth-to-plastic hinge and equivalent plastic-hinge length is essential for reliable assessment of ductility capacity. Available recommendations for these parameters have resulted in contradicting conclusions due to numerical simplifications and/or experimental limitations. In this study, basic concepts of strain wedge model are employed to provide guidelines for the estimation of the key parameters by incorporating nonlinear behavior of the soil-pile system. A set of dimensionless design charts is produced based on an analytical approach covering a range of practical values of soil and pile properties. Finally, the performance of the proposed analytical model in assessing the local curvature ductility of a bridge system induced by an imposed displacement ductility factor is demonstrated through two examples. Highlights: Simplified assessment of ductility capacity for extended pile shafts based on equivalent cantilever method. Estimation of key parameters of equivalent cantilever model incorporating nonlinear behavior of soil-pile system. Design guidelines for cast-in-drilled-hole (CIDH) reinforced concrete piles using basic concepts of strain wedge model.